(untitled) (Medical Forum Monthly, 2024)
Objective: To analyze the histological type, gender and site distribution of different jaw lesions at liaquat university hospital Hyderabad. Study Design: A Retrospective Study Place and Duration of Study: This study was conducted at the Liaquat University Hospital from January 2011 to January 2013 Materials and Methods: 126 patients having different jaw lesions treated at Liaquat University Hospital was carried out. Data was analyzed by SPSS Version 16. Results: In this study the most common lesion were odontogenic cysts 67 cases, followed by 20 cases of odontogenic tumors, 14 cases of fibro-osseous lesions, 12 cases of giant cell lesions, 6 infectious lesions and 5 non-odontogenic cysts, 2 cases of non-odontogenic tumor. 83 patients were males and 43 were females. The mandible was involved in 82 cases and the maxilla in 44 cases. Conclusion: Study shows that odontogenic cysts were found to be the common jaw lesions. Males were predominantly affected and mandible was more commonly involved than maxilla.